1995
DOI: 10.5014/ajot.49.5.397
|View full text |Cite
|
Sign up to set email alerts
|

Occupationally Embedded Exercise Versus Rote Exercise: A Choice Between Occupational Forms by Elderly Nursing Home Residents

Abstract: Results were consistent with the hypothesis that elderly nursing home residents would tend to choose the occupationally embedded exercise. To further confirm this basic premise of occupational therapy, future studies that investigate therapeutic patterns of movement embedded in common occupations are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
1
8
1
Order By: Relevance
“…Based on a review of kinematic studies (Lin, Tang, Chen, Wu, & Shen, 2001;Lin, Wu, & Trombly, 1998;Trombly & Wu, 1999), we believed it was important to measure functional reach during a goal-directed task instead of during a rote task where participants simply reached across a table. A goal-directed task produces a higher quality of movement and is more concrete and purposeful (Lin, Wu, & Trombly, 1998;Zimmerer-Branum & Nelson, 1995) as compared to a rote task that is more abstract and artificial (Zimmerer-Branum & Nelson). Individuals are more likely to recognize and to complete a task when it is viewed as goal directed.…”
Section: Instrumentsmentioning
confidence: 98%
“…Based on a review of kinematic studies (Lin, Tang, Chen, Wu, & Shen, 2001;Lin, Wu, & Trombly, 1998;Trombly & Wu, 1999), we believed it was important to measure functional reach during a goal-directed task instead of during a rote task where participants simply reached across a table. A goal-directed task produces a higher quality of movement and is more concrete and purposeful (Lin, Wu, & Trombly, 1998;Zimmerer-Branum & Nelson, 1995) as compared to a rote task that is more abstract and artificial (Zimmerer-Branum & Nelson). Individuals are more likely to recognize and to complete a task when it is viewed as goal directed.…”
Section: Instrumentsmentioning
confidence: 98%
“…These qualitative studies broaden the quasi-experimental research on occupational meaning in older adults which examined meaning and purpose in terms of product-oriented or non product-oriented activity where meaning and purpose were determined by researchers who manipulated variables in task performance and occupational form (Hsieh, Nelson, Smith & Petersen (1996;Thibodeaux & Ludwig, 1988;Zimmerer-Branum & Nelson, 1995).…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…Thomas (1996) found that subjects who participated in materials-based occupation performed significantly more repetitions of the required body movement, thus suggesting that if a goal is to improve strength and endurance, creating conditions that encourage many repetitions would be advantageous. Zimmerer-Branum and Nelson (1995) examined the preferences of elderly nursing home residents when presented with an occupationally embedded exercise of unilaterally dunking a small spongy ball into a basketball hoop versus a rote exercise that involved moving the arm above the head in a simulation of the dunking exercise. Results were consistent with their hypothesis that elderly nursing home residents would tend to choose the occupationally embedded exercise.…”
Section: Literature Reviewmentioning
confidence: 99%